TOKOH PEMIKIR EKONOMI ISLAM PADA PERIODE KETIGA DAN KONTEMPORER - Nadzira Putri Andani; Nurhasanah Siregar; Aldy Fauzan; Maryam Batubara (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
Islamic economic thought cannot be separated from the development of Islamic history. And the development of thinking regarding Islamic economics continues to develop. In the development of Islamic economics, there are certainly many Islamic thinkers who convey their theories regarding existing economic activities. And in this research, the researcher tried to examine how systematic Islamic economic thinking was by Islamic thinkers in the third period and in the contemporary era. The Islamic economic thinkers analyzed are Shah Waliullah, Jamaluddin Al-Afghan, Muhammad Abduh, and Muhammad Iqbal and in the contemporary period those analyzed are Muhammad Abdul Mannan, Syed Nawab Haedir Naqvi, Monzer Kahf, Umer Chapra and Timur Kuran. And in this research we used qualitative research methods and the type of data used was library research by collecting reading sources related to the title being researched.